Early rehabilitation after elective total knee arthroplasty - Lisi, Claudio (Acta Biomed, 2017)
Background and aim of the work: Outcomes after TKA surgery are supposed to be related to the intensity and type of post-operative rehabilitation. Aim of this paper is to describe our early rehabilitation protocol following TKA with mini-invasive surgery in the immediate post-operative period and analyze functional recovery and changes in pain scores in these patients. Methods: in this observational study, data were collected on 215 total knee arthroplasty patients referred to Orthopedics and Traumatology inpatient ward from July 2012 to January 2014, treated with the same early start rehabilitation protocol. We recorded times to reach functional goals (sitting, standing and assisted ambulation) and pain after the treatment. Results: length of hospital stay in TKA was 4.6±1.8 days, with a rehabilitation treatment lenght of 3.3±1.3 days. The mean time needed to achieve the sitting position was 2.3±0.7 days, to reach the standing position was 2.6±1.0 days to reach the walking functional goal was 2.9±1.0 days. Pain NRS scores remained below 4 in the first and second post-operative day and below 3 from the third post-operative day. Conclusion: Our study confirms that rehabilitation started as soon as 24 hours after surgery with mini-invasive approach, enables early verticalization of patients and early recovery of walking with a good control of pain. (www.actabiomedica.it)